2020
DOI: 10.1071/bt19077
|View full text |Cite
|
Sign up to set email alerts
|

Carving up Australia's arid zone: a review of the bioregionalisation of the Eremaean and Eyrean biogeographic regions

Abstract: The Eremaean region, Australia’s arid biome and biogeographic region, has been discussed by botanists (and as the Eyrean, its counterpart for zoogeographers) for over 150 years, yet little progress was made in defining it as an area of endemism until the 2000s. As Australia’s largest biome and biogeographic region, the Eremaean has been defined in a climate sense, but is a historically composite biogeographic area. Taxa that inhabit the Eremaean (Eyrean) tend to display sister relationships to those outside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…phylogenetic clade H) are, with few exceptions including Bontia, Myoporum and a small number of Eremophila species, distributed in arid/semi-arid regions of Australia ( Figure S3). The complex evolutionary history and spatially heterogenous nature of Australia's arid zone is now being recognised [46,47], although dividing the arid biome into smaller areas for biogeographic analysis remains problematic [48]. In the present study, clear geographic patterns emerge between phylogenetic clades A-H ( Figure S3).…”
Section: Resin Chemistry As a Key Strategy To Adapt To The Eremean Zonementioning
confidence: 57%
“…phylogenetic clade H) are, with few exceptions including Bontia, Myoporum and a small number of Eremophila species, distributed in arid/semi-arid regions of Australia ( Figure S3). The complex evolutionary history and spatially heterogenous nature of Australia's arid zone is now being recognised [46,47], although dividing the arid biome into smaller areas for biogeographic analysis remains problematic [48]. In the present study, clear geographic patterns emerge between phylogenetic clades A-H ( Figure S3).…”
Section: Resin Chemistry As a Key Strategy To Adapt To The Eremean Zonementioning
confidence: 57%
“…The majority of species in Myoporeae (i.e., phylogenetic clade H) are, with few exceptions including Bontia , Myoporum , and a small number of Eremophila species, distributed in arid/semi‐arid regions of Australia (Figure S9 , for a visual representation of a number of major climatic variables in Australia see Figure S10 ). The complex evolutionary history and spatially heterogenous nature of Australia’s arid zone is now being recognized (Byrne et al., 2008 ; Murphy et al., 2019 ), although dividing the arid biome into smaller areas for biogeographic analysis remains problematic (Ebach and Murphy, 2020 ). In the present study, clear geographic patterns emerge between phylogenetic clades A–H (Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have found that different biogeographic templates, encompassing those both qualitative and quantitative perspectives, were mostly congruent with each other (Bloomfield, Knerr, & Encinas-Viso, 2018; González-Orozco, Laffan, Knerr, & Miller, 2013; González-Orozco, Thornhill, Knerr, Laffan, & Miller, 2014). Yet, even when applying similar biogeographic approaches to partition Australia’s landscape, phyto- and zoo-geographers disagreed on the boundaries of some areas of Australia, such as the arid region (Ebach & Murphy, 2020). In our algorithmic, data-driven model, the partition of arid Australia is greater than in any of the bioregionalization scenarios of Bloomfield et al (2018).…”
Section: Discussionmentioning
confidence: 99%